The Academics Writing Of The Admissibility Of Digital Documents In Court Of Malaysia: The Literature Analysis - Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Lukman Abdul Mutalib; Nurul Syazwani Abdullah Kahar (Usuli Faqih Research Centre PLT., 2024)
Indexed by MyCite